Bibliometric Analysis: Physics Online Learning in Indonesia (2020-2021) - Permadi, Dimas; Tiarto, Eko Hari (CV FOUNDAE, 2022)
This study aims to identify research trends in online learning physics subjects from 2020 to 2021, as well as research recommendations to improve the quality of online learning physics. The method employed is quantitative and includes bibliometric analysis. It was obtained from the Google Scholar database using Harzing's publish or perish application, and data was analyzed using VOSviewer. Searches with online learning physics yielded 70 articles, which were then examined. According to the research findings, quantitative research is the most commonly employed method, followed by qualitative research. The collected study focuses mainly on learning, physics, online learning, and learning outcomes. Learning challenges, effectiveness, critical thinking, Google Classroom, learning media, interest in learning, and motivation to study are suggested research subjects for possible online physics learning.